Tomorrow's world = Le monde de demain = Die welt von morgen = De wereld van morgen - Cerimedo, Carolina; Cillero & de Motta (Belgium : Booqs, 2011)
Flying cars, impossibly-shaped homes, ultrasonic travel - imagining the future has always fascinated creative people and explains why futuristic themes are often at the heart of style and fashion. This book demonstrates and comprehensively illustrates how designers and architects of today imagine and create tomorrow's world.
Text in English, French, German and Dutch.
Keywords: Sustainable design -- Pictorial works; Sustainable architecture -- Pictorial works; Minimal design -- Pictorial works; Minimal architecture -- Pictorial works